1998
DOI: 10.1089/thy.1998.8.311
|View full text |Cite
|
Sign up to set email alerts
|

Possible Involvement of Fas-Mediated Apoptosis in Eye Muscle Tissue from Patients with Thyroid-Associated Ophthalmopathy

Abstract: In order to investigate the possible involvement of apoptosis in the pathogenesis of thyroid-associated ophthalmopathy (TAO), we studied the expression of Fas, Fas ligand (FasL), and Bcl-2 in extraocular muscle tissues from patients with TAO by immunohistochemistry using monoclonal antibodies against Fas, FasL, and Bcl-2. Apoptosis was detected by in situ end-labeling of fragmented DNA. Apoptosis was detected in extraocular muscle tissues from 17 of 19 patients with TAO and, to a smaller degree in 4 of 7 norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…It is also possible that some percentage of these activated satellite cells may apoptose and never integrate into existing myofibers. Our laboratory and others have recently demonstrated that there a certain amount of apoptosis that occurs in normal, uninjured adult rabbit 9 and human 39 EOMs, and this has been corroborated by the presence of apoptotic markers demonstrated by expression profiling. 40 However, the demonstrated occurrence of myonuclear addition into uninjured myofibers of EOMs in both mature rabbits 7 and mice 8 certainly supports the notion that at least some, if not most of these activated satellite cells would follow the same pathway in both human and monkey EOM and fuse into existing myofibers.…”
Section: Resultsmentioning
confidence: 54%
“…It is also possible that some percentage of these activated satellite cells may apoptose and never integrate into existing myofibers. Our laboratory and others have recently demonstrated that there a certain amount of apoptosis that occurs in normal, uninjured adult rabbit 9 and human 39 EOMs, and this has been corroborated by the presence of apoptotic markers demonstrated by expression profiling. 40 However, the demonstrated occurrence of myonuclear addition into uninjured myofibers of EOMs in both mature rabbits 7 and mice 8 certainly supports the notion that at least some, if not most of these activated satellite cells would follow the same pathway in both human and monkey EOM and fuse into existing myofibers.…”
Section: Resultsmentioning
confidence: 54%
“…3,50 Clinical reports have well documented that apoptosis is involved in a variety of muscle Wild-type Bax -/-disorders including spinal muscular myopathies, peripheral neuropathies, amyotrophic lateral sclerosis, muscle dystrophies, metabolic/mitochondrial myopathies, inflammatory myopathies, congenital myopathies, distal myopathies, thyroid-associated ophthalmyopathies, chronic heart failure-associated myopathies, critical ill myopathies, and burn injury-associated muscle wasting. 3,4,7,8,[51][52][53][54][55][56][57][58][59] A recent study clearly demonstrated that inhibition of apoptosis improves the outcome of skeletal muscle wasting pathology in the genetically knockout mice that were deficient of the laminin-α2 gene, an animal model of congenital muscular dystrophy. 60 By adopting genetic intervention by crossbreeding the laminin-α2-deficient mice with pro-apoptotic Bax-deficient mice or with mice carrying the muscle-specific anti-apoptotic Bcl-2 transgene, Girgenrath and colleagues 60 have shown that the extent of muscle pathology is ameliorated by either inactivation of the pro-apoptotic protein Bax or overexpression of the anti-apoptotic protein Bcl-2.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies to the other eye muscle antigens might then represent a secondary phenomenon after eye muscle damage and antigen exposure. Recently, evidence of Fas-mediated apoptosis was provided in extraocular muscle tissue from GO patients (75), but this is likely to represent a late event in the course of eye disease, preceding fibrotic changes in eye muscles.…”
Section: Pathogenesismentioning
confidence: 99%